The Place to Purchase Drugs for Community Self-Medication at Green Hills Moncongloe Housing, Maros Regency - Asrina, Rina; Roosevelt, Alfreds; Julyiansyah, Arqian (Politeknik Sandi Karsa, 2023)
Self-medication or self-medication is part of the community's efforts to treat minor ailments by using over-the-counter drugs, limited over-the-counter drugs and mandatory pharmacy drugs without consulting a doctor first. Most people self-medicate because they don't have time to go to the doctor, the distance to the puskesmas, hospital or doctor's office is far from home. So that people choose where to buy drugs at pharmacies, grocery stalls, minimarkets and drugstores. The purpose of this study was to find out where to buy drugs for self-medication in the Green Hills Moncongloe Housing Complex, Maros Regency. The method used in this research is descriptive method, namely research that includes surveys with data collection techniques in the form of questionnaires. This research was conducted at the Green Hills Moncongloe Housing Complex, Maros Regency which was carried out in February - March 2023 by distributing questionnaires to 50 respondents. From the results of the study it can be seen that of the 50 respondents, 29 people (58%) bought drugs at pharmacies, 16 people (32%) at grocery stalls, 3 people (6%) minimarkets, and finally 2 people (4%) drugstores. So it can be concluded that more people choose places to buy medicines at pharmacies because people believe that medicines sold at pharmacies can be trusted for their quality and authenticity and the public can obtain information about the drugs they buy.